Oral or written feedback to improve written production at the university - Trejo Sare, Jenny Evelyn (2021)
The objective of this article is to publicize the importance of feedback (oral or written, in person or using technology) as a teaching strategy that can be used by teachers, to help university  students improve their academic writing. The difficulties that university students face in producing academic texts is a problem that, if not treated by teachers, either rethought about their strategies, researching new ones, and especially acting, can severely influence the student’s performance to such an extent that he or she may be inclined to dropout. Taking into account the problem, it explains how feedback, which is part of the formative assessment, allows meaningful learning to be achieved, as it is not only a bug review but a way to avoid making them in the future. To do this, based on some research such as Those of Cuevas-Solar and Arancibia, Padilla and López, and Alvarez and Difabio de Anglat, proposes the ideal characteristics of a feedbackthat facilitates the improvement of academic writing: application of feedback and feedforward, personalized, multidirectional and innovative. It also details the positive results of this strategy in the performance of academic writing. And finally, the importance of applying feedback is made known as a simple strategy to apply by teachers to achieve the goal of the student developing his or her ability to produce academic texts.